Scenarios for Nuclear Fusion in Palladium-Deuterium Alloys at Ambient Temperature - Christian K. Jørgensen (CHIMIA)
The quantum aspects of exothermic reactions in palladium-deuterium alloys possibly also containing lithium and/or exotic systems X⊖ or X⊕ (discussed by Glashow, Cahn, and the writer in 1981[12,13]) are highlighted.